Economic burden of multimorbidity in patients with severe asthma: a 20-year population-based study. Issue 12 (18th September 2019) - Chen, Wenjia; Safari, Abdollah; FitzGerald, J Mark; Sin, Don D; Tavakoli, Hamid; Sadatsafavi, Mohsen
Abstract : Background: The economic impact of multimorbidity in severe or difficult-to-treat asthma has not been comprehensively investigated. Aims: To estimate the incremental healthcare costs of coexisting chronic conditions (comorbidities) in patients with severe asthma, compared with non-severe asthma and no asthma. Methods: Using health administrative data in British Columbia, Canada (1996–2016), we identified, based on the intensity of drug use and occurrence of exacerbations, individuals who experienced severe asthma in an incident year. We also constructed matched cohorts of individuals without an asthma diagnosis and those who had mild/dormant or moderate asthma (non-severe asthma) throughout their follow-up. Health service use records during follow-up were categorised into 16 major disease categories based on the International Classification of Diseases. Incremental costs (in 2016 Canadian Dollars, CAD1=US0.75=₤0.56=€0.68) were estimated as the adjusted difference in healthcare costs between individuals with severe asthma compared with those with non-severe asthma and non-asthma. Results: Relative to no asthma, incremental costs of severe asthma were 2779 per person-year (95% CI 2514 to 3045), with 54% (1508) being attributed to comorbidities. Relative to non-severe asthma, severe asthma was associated with incremental costs of 1922 per person-year (95% CI 1670 to 2174), with 52% (1003) being attributed to comorbidities. In both cases, the most costly comorbidity was respiratory conditions other than asthma (468 (17%) and 451 (23%), respectively). Conclusions: Comorbidities accounted for more than half of the incremental medical costs in patients with severe asthma. This highlights the importance of considering the burden of multimorbidity in evidence-informed decision making for patients with severe asthma.